2017
DOI: 10.1080/23802359.2017.1307702
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the sooty swift (Cypseloides fumigatus)

Abstract: We assembled the mitogenome of Cypseloides fumigatus based on off-target sequences from ultraconserved elements sequencing. We found a total length of 16,850 bp, including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and one control region, organized in the standard avian gene order. We have built a phylogenetic tree including 26 species of swifts that suggested C. fumigatus as sister species of C. cryptus, and indicated exciting opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…To date, genetic studies that included the Black Swift focused on phylogeny and barcoding of swifts and swiftlets rather than on intraspecific genetic variation, parentage or geneticsbased ecological questions (Sibley & Ahlquist 1990, Lee et al 1996, Holmgren 1998, Price et al 2004, Schindel et al 2011). There are few molecular studies on the Cypseloidinae swifts (Biancalana et al 2017(Biancalana et al , 2019 and there are no published accounts of molecular methods employed to determine mating strategies or parentage in any western hemisphere swift species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, genetic studies that included the Black Swift focused on phylogeny and barcoding of swifts and swiftlets rather than on intraspecific genetic variation, parentage or geneticsbased ecological questions (Sibley & Ahlquist 1990, Lee et al 1996, Holmgren 1998, Price et al 2004, Schindel et al 2011). There are few molecular studies on the Cypseloidinae swifts (Biancalana et al 2017(Biancalana et al , 2019 and there are no published accounts of molecular methods employed to determine mating strategies or parentage in any western hemisphere swift species.…”
mentioning
confidence: 99%
“…There are few molecular studies on the Cypseloidinae swifts (Biancalana et al . 2017, 2019) and there are no published accounts of molecular methods employed to determine mating strategies or parentage in any western hemisphere swift species.…”
mentioning
confidence: 99%
“…Although vauxi, pelagica, and chapmani (including viridipennis) have often been considered closely related (American Ornithologists' Union [1983] and Marín [1997] suggested that they form a superspecies), and although vauxi, pelagica, and chapmani are sister species in our nuclear analyses, chapmani is sister to the andrei/meridionalis/brachyura clade in our mitochondrial and combined trees (cf. Biancalana et al 2017). This circumstance, in which the mitochondrial data contradict both nuclear and traditional phenotypic data, may be the result of stochasticity in lineage sorting affecting the mtDNA.…”
mentioning
confidence: 99%